2016
DOI: 10.1142/s0218216516410133
|View full text |Cite
|
Sign up to set email alerts
|

Knots in knots: A study of classical knot diagrams

Abstract: Looking at the structure of minimal prime knot presentations, one can notice that there are often, perhaps always, segments that present either the trefoil or the figure-eight knot. This note explores the question as to whether this is always the case, reporting on conversations with Jablan Slavik that began at a 2009 conference in Trieste, Italy and which never reached a conclusion. Evidence supporting this conjectured presence is reported and potential consequences are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Supplemented by a careful visual analysis of the remaining cases, it seemed that all prime knots contained either a trefoil or a figure-eight knot or both. The resulting data lead to the conjectures proposed in the 2009 lecture and the research reported in [6] and this note.…”
Section: Historical Perspectivessupporting
confidence: 77%
See 4 more Smart Citations
“…Supplemented by a careful visual analysis of the remaining cases, it seemed that all prime knots contained either a trefoil or a figure-eight knot or both. The resulting data lead to the conjectures proposed in the 2009 lecture and the research reported in [6] and this note.…”
Section: Historical Perspectivessupporting
confidence: 77%
“…This data lead to the conjectures proposed in the 2009 lecture. Slavik Jablan and Ken Millett explored these conjectures from which a more precise interpretation of the conjectures was formulated as reported in [6]. In this report, the preliminary results of a computer implementation of the refined analysis of all prime knots through 16 crossings was reported.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations